2019
DOI: 10.1542/hpeds.2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Experiences During “Boarding” Hospitalization While Awaiting Inpatient Psychiatric Treatment Following Suicidal Ideation or Suicide Attempt

Abstract: BACKGROUND: Two million adolescents experience suicidal ideation (SI) or suicide attempt (SA) annually, and they frequently present to emergency departments. Delays in transfer to inpatient psychiatric units increasingly lead to "boarding" in emergency departments and inpatient medical units. We sought to understand adolescents' perspectives during boarding hospitalizations to gain insight into helpful practices and targets for improvement. METHODS: Using convenience sampling, we conducted semistructured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 18 publications
3
45
0
1
Order By: Relevance
“…It has been discussed, that the admission to emergency care due to suicidal behavior can be a stressful situation for those seeking acute care (21), especially if specialized services for youth are lacking (22). Youth stressed the importance of information and compassionate clinicians in this situation, and stated that repeated questioning from different clinicians was perceived as negative (23). Due to the retrospective nature of our analysis, we were not able to provide information about patients´experiences with emergency psychiatric care, although this would clearly help to inform future optimization of assessment and treatment in these situations from a customer´s viepoint.…”
Section: Discussionmentioning
confidence: 99%
“…It has been discussed, that the admission to emergency care due to suicidal behavior can be a stressful situation for those seeking acute care (21), especially if specialized services for youth are lacking (22). Youth stressed the importance of information and compassionate clinicians in this situation, and stated that repeated questioning from different clinicians was perceived as negative (23). Due to the retrospective nature of our analysis, we were not able to provide information about patients´experiences with emergency psychiatric care, although this would clearly help to inform future optimization of assessment and treatment in these situations from a customer´s viepoint.…”
Section: Discussionmentioning
confidence: 99%
“…In 5 of the remaining 7 studies, the authors defined boarding on the basis of transfer to an inpatient pediatric medical unit after medical clearance while awaiting an inpatient psychiatric bed. 23,25,27,29,32 Lastly, Campbell and Pierce 22 and Conrad et al 24 evaluated boarding in the ED only, defining boarding as the time from disposition decision or medical clearance in the ED until admission or transfer.…”
Section: Figurementioning
confidence: 99%
“…26,27 Wharff et al 31 reported that patients presenting overnight had 6.2 times the odds of boarding as those presenting from 8:00 AM to 12:00 PM, whereas significant time-of-day effects were not found in the analysis by Hoffmann et al 26 In 4 studies, authors reported processes or outcomes associated with pediatric mental health boarding beyond boarding duration and frequency. [23][24][25]32 finding that 33% of youth had improvements in their functioning during the boarding period. 25 Beyond these clinical process and outcome measures, Claudius et al 23 examined inpatient hospital costs associated with boarding, estimating an average inpatient hospital cost of $4269 per boarded patient.…”
Section: Figurementioning
confidence: 99%
“…The adolescents in this study confirmed this by sharing experiences of being motivated by trust and freedom as they were able to adjust BA according to their own terms. The relief from typical uncertainties of psychiatric hospitalization, including not knowing what to expect and facing repeated questioning [ 35 ], provided predictability. This is recognized from research on BA for adults, who described access to BA as a relief from fear of rejection or of being questioned [ 18 , 36 ].…”
Section: Discussionmentioning
confidence: 99%